2017
DOI: 10.1186/s12889-017-4148-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial determinants of HIV testing across stages of change in Spanish population: a cross-sectional national survey

Abstract: BackgroundThe goal of this research is to study the psychosocial determinants of HIV-testing as a function of the decision or change stage concerning this health behavior. The determinants considered in the major ongoing health models and the stages contemplated in the Precaution Adoption Process Model are analysed.MethodsA cross-sectional survey was administered to 1,554 people over 16 years of age living in Spain by a computer-assisted telephone interview (CATI). The sample design was randomised, with quotas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Those individuals who were motivated to take the test for feeling sick, and those who took the test occasionally, almost never or never had a better chance of being diagnosed late. Periodic screening for the virus is related to people's perception of the health-disease process and of their vulnerability to HIV, as well as to their access to the health services that offer the test (39,42) . and acting in relation to effective prevention in order not to get sick (43) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those individuals who were motivated to take the test for feeling sick, and those who took the test occasionally, almost never or never had a better chance of being diagnosed late. Periodic screening for the virus is related to people's perception of the health-disease process and of their vulnerability to HIV, as well as to their access to the health services that offer the test (39,42) . and acting in relation to effective prevention in order not to get sick (43) .…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for LD are the absence or low perception on the risk on the part of vulnerable people ( 38 - 39 ) . Generally, people with a steady affective partnership, due to the low perception of risk ( 37 ) , use condoms less frequently during sexual intercourse, which makes them vulnerable to HIV ( 40 ) and to late diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that FSW had low intention to regularly test for syphilis, perhaps because of limited knowledge of the benefits of periodic STI testing. Behavioural intentions are reported to explain up to 30-50% of the variance in health seeking behaviours including STI testing [22][23][24]37]. Studies have found that negative attitudes, low perceived benefits and lack of knowledge of screening guidelines are associated with low screening intentions [28,[38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Intention is a major determinant of health behavior including participation in health screening programs [22][23][24][25]. Intention or motivation to adopt STI and HIV testing by FSW on a regular basis may be influenced by personal beliefs, knowledge, experiences, social environment, quality of services and quality of interaction with service providers, which interact to predict FSW motivation to adopt regular STI and HIV testing behavior [19,26].…”
mentioning
confidence: 99%
“…All the items for sections B and C were developed based on literature review, [12][13][14][15] HBM, 8 and discussions with a family physician. The questionnaire's content validation was tested by a panel of experts consisting of two family physicians with a particular interest in men's health and one clinical psychologist.…”
Section: Methodsmentioning
confidence: 99%